Compete to Learn: Toward Cybersecurity as a Sport - TJ OConnor; Dane Brown; Jasmine Jackson; Bryson Payne; Suzanna Schmeelk (Journal of Cybersecurity Education, Research & Practice)
To support the workforce gap of skilled cybersecurity professionals, gamified pedagogical approaches for teaching cybersecurity have exponentially grown over the last two decades. During this same period, e-sports developed into a multi-billion dollar industry and became a staple on college campuses. In this work, we explore the opportunity to integrate e-sports and gamified cybersecurity approaches into the inaugural US Cyber Games Team. During this tenure, we learned many lessons about recruiting, assessing, and training cybersecurity teams. We share our approach, materials, and lessons learned to serve as a model for fielding amateur cybersecurity teams for future competition.